Qualidade do serviço de informação digital :um estudo exploratório em web sites de Programas de Pós-Graduação - Oliveira, Adriana Carla Silva de (2006)
This dissertation of Mestrado investigated the performance and quality of web sites. The target of the research is the proposal of an integrated model of evaluation of services of digital information in web educational sites. The universe of the research was constituted by eighteen Brazilian Universities that offer after-graduation courses, in the levels of mestrado and doutorado in the area of Engineering of Production. The adopted methodology was a descriptive and exploratory research, using the technique of systematic comment and focus group, for the collection of the data, using itself changeable independent dependents and, through the application of two instruments of research. The analysis protocol was the instrument adopted for evaluation and attainment of qualitative results. E the analysis grating was applied for evaluation and attainment of the quantitative results. The qualitative results had identified to the lack of standardization of web sites, under the attributes of content, hierarchy of information, design of the colors and letters. It of accessibility for carriers of auditory and visual special necessities was observed inexistence, as well as the lack of convergence of medias and assistivas technologies. The language of the sites also was evaluated and all present Portuguese only language. The general result demonstrated in grafico and tables with classification of the Universities, predominating the Good note As for the quantitative results, analysis method ed was estatistico, in order to get the descriptive and inferencial result between the dependent and independent variaveis. How much a category of analysis of the services of the evaluated sites, was found it props up and the index generality weighed. These results had served of base for ranking of existence or inexistence the Universities, how much of the information of services in its web sites. In analysis inferencial the result of the test of correlation or association of the independent variaveis (level, concept of the CAPES and period of existence of the program) with the caracteristicas, called was gotten categories of services. For this analysis the estatisticos methods had been used: coefficient of Spearman and the Test of Fisher. But the category you discipline of the Program of Mestrado presented significance with variavel independent and concept of the CAPES. Main conclusion of this study it was ausencia of satandardization o how much to the subjective aspects, design, hierarchy of information navigability and content precision and the accessibility inexistence and convergence. How much to the quantitative aspects, the information services offered by web sites of the evaluated Universities, still they do not present a satisfactory and including quality. Absence of strategies, adoption of tools web, techniques of institucional marketing and services that become them more interactive, navigable is perceived and with aggregate value